2016
DOI: 10.3906/kim-1606-5
|View full text |Cite
|
Sign up to set email alerts
|

Chromium redox speciation in food samples

Abstract: Chromium is an element with important biological characteristics, depending on its different species. Cr(III) is considered as essential; however, the Cr(VI) form is classified as carcinogenic. For this reason, speciation analysis in food samples is a very important question. The proposed data procedures for chromium redox speciation in the literature can be divided into those with the use of online hyphenated techniques and those where appropriate sample pretreatment is necessary. The strategies for nonchroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…Trivalent chromium in yogurt and cheese samples ranges approximately from <13 to 255 ng/g. Most studies suggested the absence of hexavalent chromium in food samples like dairy and cereal products [ 37 ], chocolates, beverages, vegetables, fruits, eggs, meat and sea products [ 38 ], and flour [ 39 ], similar to the results from toy sample analyses obtained in this study.…”
Section: Resultssupporting
confidence: 86%
“…Trivalent chromium in yogurt and cheese samples ranges approximately from <13 to 255 ng/g. Most studies suggested the absence of hexavalent chromium in food samples like dairy and cereal products [ 37 ], chocolates, beverages, vegetables, fruits, eggs, meat and sea products [ 38 ], and flour [ 39 ], similar to the results from toy sample analyses obtained in this study.…”
Section: Resultssupporting
confidence: 86%
“…For the temperature optimization, the complexation of Cr(III) and Cr(VI) was carried out at 30, 50, 70 and 90 °C, respectively (duplicate analysis) using a reaction time of 25 min. It turned out that the complexation of both Cr(III) and Cr(VI) is incomplete at 30 °C while at 90 °C, consistent oxidation of Cr(III) to Cr(VI) occurs (not shown here), which is in agreement with other studies [6,43]. Quantitative derivatisation reactions of Cr(III)-EDTA (101%) and Cr(VI)-DPC (98%) was obtained at 70 °C.…”
Section: Optimization Of the Reaction Temperature And Timesupporting
confidence: 92%
“…Cr(III) is poorly soluble and relatively immobile in aqueous environments compared to Cr(VI), which is highly mobile, soluble and consequently, more bioavailable [4,5]. Cr(VI) has been recognized for several decades as being carcinogenic, whereas Cr(III) was for a long time considered as a beneficial element for the human health [6]. Nevertheless, the European Food Safety Authority (EFSA) stated relatively recently that there is no convincing evidence of beneficial effects of Cr(III) for healthy people [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accompanied by the development of modern industry, water contamination problem occurs in daily life and seriously endangers the safety of human beings and other bio‐organisms. To eliminate the contaminants in water, a wide range of technologies have been developed, including ozonation, [1] microbial degradation, [2] photocatalytic degradation, [3,4] membrane filtration, [5] adsorption, [6–8] etc. Among these, adsorption is recognized as a preferable method because of its simple operation and economical properties [9] .…”
Section: Introductionmentioning
confidence: 99%